Experimental Study on Heating Performance of Air-source Heat Pump Coupled with a New Type Radiant Floor - Gao Feng; Wang Yu; Li Yanju; Li Shengying; Guo Chunmei (Zhileng xuebao)
In order to analyze the actual heating effect and operation performance of a new type of radiant floor heating system coupled with air-source heat pump applied in the northern cold area, a 76-day field test was conducted in an office building for the management of residential area in Tianjin. During the test period, the average temperature of indoor working area was 18.4~21.8 ℃, and the average indoor surface temperature was 22.5~29.1 ℃. More than 90% of indoor LPD1 and LPD2 were in grade I index. The average daily heating capacity and power are 1.5~6.9 kW and 0.6~3.2 kW, respectively; the daily average power consumption is 0.79 kW?h/m2, and the daily average COP is 1.43~3.54. When the temperature difference between the floor surface and the the office area is within 5 ℃, the heat dissipation can still reach 50–100 W/m2. In the coldest test days, the outdoor temperature is -10.1~2.1 ℃, the average temperature in the working area of three indoor test positions is 21.4 ℃, the lowest indoor instantaneous temperature is 16.4 ℃, LPD1 and LPD2 are all in the standard range of grade I and II, which ensures the heating quality. The range of the heating capacity and power of the system is 6.1~10.9 kW and 2.9~3.3 kW, respectively, and the range of COP is 1.91~3.49.